ANALYSIS OF CIVIL SOCIETY CIVIC CULTURE IN REALIZING THE QUALITY OF THE 2024 ELECTION - Purba, Darmawan; Juantara, Bendi; Krisbintoro, R. Sigit; Rosalia, Feni (Department of Government, FISIP, Universitas Padjadjaran, 2025)
The quality of elections in emerging democracies is increasingly understood as a social outcome rather than a purely procedural achievement. This study examines how civic culture within civil society shapes public perceptions of the quality of the 2024 General Election in Lampung Province, Indonesia. Drawing on Civic Culture Theory, the study analyzes the configuration of civil society actors, civic orientations, and their implications for electoral quality at the subnational level. The research adopts a qualitative approach with a mixed-methods logic based on triangulation, combining in-depth interviews with civil society actors, election stakeholders, and observers, alongside a descriptive public opinion survey. The findings reveal an ambivalent role of civil society in the electoral process. Although procedural awareness and voter participation are high, evaluative civic orientations remain weak, reflected in the normalization of money politics and the dominance of symbolic and affective political mobilization. Public deliberation is fragmented and largely confined to elite spaces, resulting in elections perceived as procedurally orderly but substantively contested. This study contributes by contextualizing Civic Culture Theory and demonstrating that electoral quality shaped by asymmetrical civic development. Limited to Lampung provincial case, this study recommends comparative and longitudinal research to further examine civic culture and electoral legitimacy.gb777